Deployment of an autonomous apparatus for measuring light scattering in deep sea - Balasi, K. G.; Domvoglou, T.; Kiskiras, I.; Lenis, D.; Maragos, N.; Stavropoulos, G. (HNPS Advances in Nuclear Physics, 2019)
The KM3NeT research infrastructure will be a deep sea multidisciplinary observatory in the Mediterranean Sea housing a neutrino telescope. Accurate knowledge of the optical properties of the sea water is important for the best performance of the telescope. In this work we describe the deployment of the equipment that we had previously examined by Monte Carlo (MC) simulations1, in the context of the “scattering experiment” in order to evaluate the parameters describing the scattering characteristics of the sea water.